Characterizing the genetic risk for Type 2 diabetes in a Malaysian multi‐ethnic cohort. Issue 10 (24th March 2015) - Abdullah, N.; Abdul Murad, N. A.; Attia, J.; Oldmeadow, C.; Mohd Haniff, E. A.; Syafruddin, S. E.; Abd Jalal, N.; Ismail, N.; Ishak, M.; Jamal, R.; Scott, R. J.; Holliday, E. G.
Abstract Aims To characterize the association with Type 2 diabetes of known Type 2 diabetes risk variants in people in Malaysia of Malay, Chinese and Indian ancestry who participated in the Malaysian Cohort project. Methods We genotyped 1604 people of Malay ancestry (722 cases, 882 controls), 1654 of Chinese ancestry (819 cases, 835 controls) and 1728 of Indian ancestry (851 cases, 877 controls). First, 62 candidate single‐nucleotide polymorphisms previously associated with Type 2 diabetes were assessed for association via logistic regression within ancestral groups and then across ancestral groups using a meta‐analysis. Second, estimated odds ratios were assessed for excess directional concordance with previously studied populations. Third, a genetic risk score aggregating allele dosage across the candidate single‐nucleotide polymorphisms was tested for association within and across ancestral groups. Results After Bonferroni correction, seven individual single‐nucleotide polymorphisms were associated with Type 2 diabetes in the combined Malaysian sample. We observed a highly significant excess in concordance of effect directions between Malaysian and previously studied populations. The genetic risk score was strongly associated with Type 2 diabetes in all Malaysian groups, explaining from 1.0 to 1.7% of total Type 2 diabetes risk variance. Conclusion This study suggests there is substantial overlap of the genetic risk alleles underlying Type 2 diabetes in Malaysian and other populations.